Creative Thinking Skills of Students on Harmonic Vibration using Model Student Facilitator and Explaining (SFAE) - Malik, Adam; Nuraeni, Yani; Samsudin, Achmad; Sutarno, Sutarno (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
This study aims to determine the implementation of learning by applying the Student Facilitator And Explaining (SFAE) model and the improvement of students' creative thinking skills on the topic of harmonic vibration. The method used in this study is pre-experimental with one-group pretest-posttest design. The samples of this study were students of class X MIA 4 SMA Karya Pembangunan I Ciaparay with a total of 30 students. The sample was chosen by random sampling technique. The field observation sheet instrument was used to observe the implementation of the SFAE model. An essay type test was given in order to measure students' creative thinking skills. This study discovers that the average implementation score of teacher’s activity was 83% which belongs to the good category and the students’ activity was 79% which belongs to the good category. The Improvement of students’ creative thinking skills based on normalized gain was 0.56 which belongs to the medium category. Hypothesis testing used was paired sample t-test with the results of t-count (36.06)> t-table (2.052). This result means that the SFAE model can be used as an alternative for improving students' creative thinking skills for the topic of harmonic vibration. Thus, implementation of the SFAE model can improve students' higher order thinking skills. The SFAE model can also be implemented for learning on other physics topics at various levels of education